Sertula florae colombiae, iii (1956)
Eschweilera papililata L. Uribe, sp. nov. / Monochaetum Bonplandii (Kunth) Naud. / Monochaetum Bonplandii (Kunth) Naud. in Ann. Sc. Nat., Sér. III, 4: 51, tab. 2 f. 1B. 1845.